2017
DOI: 10.1177/1049732317736285
|View full text |Cite
|
Sign up to set email alerts
|

Carer Experience Supporting Someone With Dementia and Cancer: A Narrative Approach

Abstract: In this article, we examine the challenges of informal carers supporting someone with dementia and cancer within the United Kingdom. Interviews were conducted with seven informal carers using a narrative approach to examine the construction of their experiences. Our findings demonstrate how informal carers navigate a path through complex cancer treatments and support their relative. A cancer diagnosis often requires multiple treatment visits to an oncology center, and this can be challenging for carers. They f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
92
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(96 citation statements)
references
References 67 publications
3
92
0
1
Order By: Relevance
“…Of the six studies included (Table ), five were conducted in the United Kingdom and one in the United States. One study used a quantitative cross sectional design, and five studies used a qualitative design . Two studies explored treatment decision making in the context of hypothetical treatment scenarios, three studies observed prospective treatment decision making in clinical scenarios, and one study interviewed patients and caregivers who were reflecting retrospectively on the cancer diagnosis and treatment decision making …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the six studies included (Table ), five were conducted in the United Kingdom and one in the United States. One study used a quantitative cross sectional design, and five studies used a qualitative design . Two studies explored treatment decision making in the context of hypothetical treatment scenarios, three studies observed prospective treatment decision making in clinical scenarios, and one study interviewed patients and caregivers who were reflecting retrospectively on the cancer diagnosis and treatment decision making …”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported their sampling method as purposive, while others were unclear . The sample sizes of interviewees reported in the qualitative studies ranged from six to 60 patient‐caregiver dyads, and seven to 23 caregivers interviewed individually . Two studies interviewed patients with dementia individually in their case sample …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations